Tecnologías inciertas: ventajas y límites de las metodologías de diseño de tecnologías mediante procesos de innovación participativos, co-creación y agilidad - Vidal-Rojas, Juan-Carlos; Cereceda-Otárola, Marcos-Rodrigo (Revista Científica, 2023)
The experience of three technology-based innovation processes is presented, applying design techniques and participatory development of technologies, co-creation techniques and agility. The analysis of the three processes accounts for the role that social researchers can play in the scaling and social articulation of the products obtained. And the role that obstacles play in development processes. It highlights the potentialities that Participatory Technology Design methodologies have in the creation of user communities, experimentation in methods with co-creation techniques and how limited agile methodologies are in some cases to create social articulations, which it reduces the possibility of success once the development process is finished.